Accumulation, metabolites formation and elimination behavior of rac-glufosinate-ammonium and glufosinate-P in zebrafish (Danio rerio) - Fei Wang; Qiao Lin; Xueqin Shi; Yunfang Li; Pengyu Deng; Yuping Zhang; Deyu Hu (Food Chemistry: X, 2022)
An efficient trace detection method for the determination of residues of the glufosinate enantiomers and metabolites in zebrafish by HPLC–Q-Exactive Orbitrap Mass Spectrometry was developed. After the purification of dichloromethane and Oasis PRiME HLB SPE column, the recovery ranges from 77% to 104%, with RSD < 10.03%. The limits of quantitation in zebrafish were 0.006–0.02 mg/kg. The results revealed zebrafish absorbed glufosinate slowly, reaching a steady state in 10–14 days, and the bioaccumulation factor (BCF) of D/L-glufosinate-ammonium was less than 0.3. L-glufosinate-ammonium accumulated preferentially in zebrafish. The residue of the metabolite N-acetyl glutamate (NAG) was smaller than that of 3-methyl phosphonic acid (MPP). D/L-glufosinate-ammonium had an elimination half-life of less than 2.3 days during the elimination phase. The bioaccumulation and elimination behavior of glufosinate-ammonium in zebrafish aquatic system was shown in this work, which offered scientific data for assessing the food safety of rac-glufosinate-ammonium and glufosinate-P (pure L-glufosinate-ammonium) in fish.